1986
DOI: 10.1002/j.1460-2075.1986.tb04316.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome walking shows a highly homologous repetitive sequence present in all the centromere regions of fission yeast

Abstract: By cloning centromere‐linked genes followed by partial overlapping hybridization, we constructed a 210‐kb map encompassing the centromere in chromosome II and a 60‐kb map near the centromere of chromosome I in the fission yeast Schizosaccharomyces pombe which has three chromosomes. Integration of the cloned sequences onto the chromosome and subsequent analyses of tetrads and dyads revealed an ∼50 kb long domain located in the middle of the 210‐kb map, tightly linked to the centromere and greatly reduced in mei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
140
1
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(147 citation statements)
references
References 42 publications
5
140
1
1
Order By: Relevance
“…To clone the prp12 ϩ gene, we transformed the prp12-1 mutant (SU102-11D) with the S. pombe genomic library constructed in cosmid pSS10 (Nakaseko et al+, 1986)+ We isolated cosmids from five independent ts4 ϩ transformants+ These cosmids were reintroduced into the SU102-11D strain, and we found rescue activity in three of five isolated cosmids+ Restriction patterns of these three cosmids shared DNA fragments of the same length, suggesting that these cosmids had an overlapping region+ The insert of cosmid #58 was subcloned into pSP1, which is the S. pombe ars1 multicopy vector (Cottarel et al+, 1993)+ In the course of subcloning, we found that cosmid #58 has a region overlapping with the cosmids used in the fission yeast genome project (Fig+ 1A)+ Because the PstI-3 fragment shown in Figure 1A has rescue activity for temperature sensitivity of prp12-1, we sequenced a gapped region between two cosmids, c27E2 and c19G12+ This 7+6-kb genomic sequence was registered in the DNA Data Bank of Japan database with the accession number AB034966+ After several steps of subcloning, we identified an NdeI fragment of 5+7 kb that complements the temperaturesensitive growth of prp12-1. Complementation of the splicing defect in prp12-1 with the NdeI 5+7-kb fragment was also verified by northern blot analysis (Fig+ 1B, lanes 8 and 9)+ The fragment was found to contain one ORF encoding a 1,206 amino acid protein (Fig+ 1A)+ To identify a mutation site in prp12-1, we amplified the corresponding ORF from prp12-1 by PCR and sequenced it+ There was a single point mutation at the nucleotide position 3340, resulting in replacement of glycine with serine at the amino acid position 1114 (Fig+ 2)+ Unexpectedly, the temperature sensitivity of prp12-1 was suppressed with the multicopy introduction of the prp12-1 mutant gene (data not shown)+ To confirm further that the isolated gene is the authentic prp12 ϩ gene and not a suppressor gene, we performed integration mapping as described in Materials and Methods+ Twenty-three asci were dissected and all the progenies showed cosegregation of prp12 ϩ and ura4 ϩ in genetic crosses, indicating that the isolated gene is not a suppressor gene (data not shown)+…”
Section: Cloning Of the Prp12 + Genementioning
confidence: 99%
“…To clone the prp12 ϩ gene, we transformed the prp12-1 mutant (SU102-11D) with the S. pombe genomic library constructed in cosmid pSS10 (Nakaseko et al+, 1986)+ We isolated cosmids from five independent ts4 ϩ transformants+ These cosmids were reintroduced into the SU102-11D strain, and we found rescue activity in three of five isolated cosmids+ Restriction patterns of these three cosmids shared DNA fragments of the same length, suggesting that these cosmids had an overlapping region+ The insert of cosmid #58 was subcloned into pSP1, which is the S. pombe ars1 multicopy vector (Cottarel et al+, 1993)+ In the course of subcloning, we found that cosmid #58 has a region overlapping with the cosmids used in the fission yeast genome project (Fig+ 1A)+ Because the PstI-3 fragment shown in Figure 1A has rescue activity for temperature sensitivity of prp12-1, we sequenced a gapped region between two cosmids, c27E2 and c19G12+ This 7+6-kb genomic sequence was registered in the DNA Data Bank of Japan database with the accession number AB034966+ After several steps of subcloning, we identified an NdeI fragment of 5+7 kb that complements the temperaturesensitive growth of prp12-1. Complementation of the splicing defect in prp12-1 with the NdeI 5+7-kb fragment was also verified by northern blot analysis (Fig+ 1B, lanes 8 and 9)+ The fragment was found to contain one ORF encoding a 1,206 amino acid protein (Fig+ 1A)+ To identify a mutation site in prp12-1, we amplified the corresponding ORF from prp12-1 by PCR and sequenced it+ There was a single point mutation at the nucleotide position 3340, resulting in replacement of glycine with serine at the amino acid position 1114 (Fig+ 2)+ Unexpectedly, the temperature sensitivity of prp12-1 was suppressed with the multicopy introduction of the prp12-1 mutant gene (data not shown)+ To confirm further that the isolated gene is the authentic prp12 ϩ gene and not a suppressor gene, we performed integration mapping as described in Materials and Methods+ Twenty-three asci were dissected and all the progenies showed cosegregation of prp12 ϩ and ura4 ϩ in genetic crosses, indicating that the isolated gene is not a suppressor gene (data not shown)+…”
Section: Cloning Of the Prp12 + Genementioning
confidence: 99%
“…However, while yeast promises to provide a fruitful model system for eentromere function, it is unlikely that the centromeres of higher eukaryotes will simply be iterations of an S. cerevisiae centromere subtmit. Even the centromeres of the fission yeast Schizosaccharomycespombe are much more complex, and involve higher order repeats of centromeric DNA (Clarke and Baum, 1990;Chikashige et al, 1989;Nakaseko et al, 1986). Electron microscopy studies have revealed that the higher eucaryotic centromere is also more complex in structural organization (Comings and Okada, 1971;Ris and Witt, 1981;Reider, 1982).…”
mentioning
confidence: 99%
“…Standard procedures for DNA preparation, restriction enzyme digestion, gel transfer and Southern hybridization were followed (13,15,16). Filters were hybridized in 5XSSPE and 0.3% SDS using 100 pg/ml salmon sperm DNA.…”
Section: Methodsmentioning
confidence: 99%
“…The nucleotide sequence organization of the centromere structure in the fission yeast Schizosaccharomyces pombe is quite different (13,14). There C I R L Press Limited, Oxford, England.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation